Label‐Free Mycotoxin Raman Identification by High‐Performing Plasmonic Vertical Carbon Nanostructures. Issue 49 (11th October 2021) - M. Santhosh, Neelakandan; Shvalya, Vasyl; Modic, Martina; Hojnik, Nataša; Zavašnik, Janez; Olenik, Jaka; Košiček, Martin; Filipič, Gregor; Abdulhalim, Ibrahim; Cvelbar, Uroš
Abstract: Mycotoxins are widespread chemical entities in the agriculture and food industries that can induce cancer growth and immune deficiency, posing a serious health threat for humankind. These hazardous compounds are produced naturally by various molds (fungi) that contaminate different food products and can be detected in cereals, nuts, spices, and other food products. However, their detection, especially at minimally harmful concentrations, remains a serious analytical challenge. This research shows that high‐performing plasmonic substrates (analytical enhancement factor = 5 × 10 7 ) based on plasma‐grown vertical hollow carbon nanotubes can be applied for immediate detection of the most toxic mycotoxins. Due to excellent sensitivity allowing operation at ppb concentrations, it is possible to collect vibrational fingerprints of aflatoxin B1, zearalenone, alternariol, and fumonisin B1, highlighting the key spectral differences between them using principal component analysis. Regarding time‐consuming conventional methods, including thin‐layer chromatography, gas chromatography, high‐performance liquid chromatography, and enzyme‐linked immunosorbent assay, the designed surface‐enhanced Raman spectroscopy substrates provide a clear roadmap to reducing the detection time‐scale of mycotoxins down to seconds. Abstract : It is reported that plasmonic substrates consisting of vertical carbon nanotubes offer a unique option for immediate and accurate mycotoxin vibrational fingerprint detection. Plasma nanoengineering improves the surface morphology, enhancing the chip's sensitivity. Consequently, optical investigations of cancer‐provoking biosphere entities are possible at ppb concentration levels, thus advancing existing food‐quality inspection equipment.